Mineral water: A microbiological approach - Falcone-Dias, Maria Fernanda [UNESP]; Emerick, Guilherme L. [UNESP]; Farache-Filho, Adalberto [UNESP] (IWA Publishing, 2012)
The microbiological quality of bottled mineral water of various domestic brands sold in Brazil was investigated, with particular focus on the heterotrophic plate count (HPC). Neither total coliforms nor Escherichia coli were found in any 1.5 L bottle samples. Total coliforms were found in 2.9% of the small bottles, while in 20 L bottles the presence of total coliforms and E. coli was demonstrated in 15.5 and 2.4% of samples, respectively. Pseudomonas aeruginosa was detected in 4.3, 4.5 and 9.5% of small, 1.5 and 20 L bottles, respectively. In 36.4% of the samples of 1.5 L bottles, the HPC was above 500 cfu/mL. This percentage of samples with an HPC above 500 cfu/mL increased to 52.0 and 61.9% in small and 20 L bottles, respectively. Higher contamination by total coliforms, E. coli, P. aeruginosa and HPCs occurred in 20 L bottles. In conclusion, several samples in this study were outside the international quality standard for mineral water and the large number of samples with high HPCs shows that more work must be done on the use of HPC in mineral water and the damaging effects that these microorganisms may cause to humans. The bottled mineral water was confirmed as a particularly important public health problem, due to the poor microbiological quality of the products that are marketed. © IWA Publishing 2012.
Keywords: Escherichia coli; Heterotrophic plate count; Mineral water; Pseudomonas aeruginosa; Total coliforms; Damaging effects; E. coli; Heterotrophic plate counts; Microbiological quality; Number of samples; P.aeruginosa; Quality standard; Bacteria; Beverages; Water; Bottles; mineral water; coliform bacterium; heterotrophy; microbial activity; public health; sampling; Brazil; colony forming unit; heterotrophic plate count; microbiological examination; nonhuman; plastic bottle; water quality